Muscle and tendon cross-sectional area and vertical stiffness in hopping - Eriksrud, O.; Ekeberg, M.; Federolf, P.; Bojsen-Moeller, J.; Raastad, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The vertical stiffness of the locomotor system during running or hopping is regulated by the tension in the muscle-tendon systems crossing the ankle, knee and hip joints. This tension is controlled by neuromuscular activation, however, it may also be influenced by the mechanical properties of the muscles or tendons. This study investigated if muscle and tendon cross-sectional area contribute to the bilateral or unilateral vertical stiffness in hopping. Methods: Seventeen athletes from different disciplines (8 power lifters, 7 distance runners, 3 high jumpers) were tested in bilateral and unilateral hopping for 15 seconds on a floor-mounted force plate (AMTI). The average vertical stiffness of 10 consecutive hopping cycles was determined according to Morin et al. (2005). The cross-sectional area of anterior and posterior thigh and leg muscles and of the patellar and Achilles tendon were obtained from MRI images. Results: Bilateral stiffness (20.7 ± 4.5 kN/m) was significantly greater than unilateral vertical stiffness (12.9 ± 4.0 and 12.1 ± 2.6 kN/m, p0.05). No significant correlations were found between bilateral and unilateral stiffness and cross-sectional area of the thigh and leg muscles or patellar and Achilles tendon. Discussion: The vertical stiffness measure in hopping reflects the overall function of the musculoskeletal system of the lower extremity where ankle (Farley and Morgenroth, 1999) and knee joint stiffness (Hobara H et al., 2009) have been found to be important. Cross-sectional area of muscles and tendons crossing these joints reflect force generation capacity, however this was not found to be correlated to vertical stiffness in this study.